Cancer care interventions for forcibly displaced populations in low- and middle-income countries of the Middle East and North African region affected by humanitarian crises: Protocol for a scoping review - Anne Lyon Havlik; Zena Ahmed; Philippa Susan Chadwick; Kate Nyhan; Kaveh Khoshnood (PLoS ONE, 2025)
Objective The objective of this scoping review is to describe and assess what cancer treatment interventions exist for forcibly displaced populations living with cancer in LMIC humanitarian settings in the Middle East and North African (MENA) region and what research has been done on these interventions. Background Humanitarian aid usually provides short-term requirements for food, shelter, and trauma relief; long-term relief focuses mainly on communicable diseases and not non-communicable diseases (NCDs) like cancer. However, no systematic search and synthesis resource of existing cancer care interventions for forcibly displaced populations in LMICs of the MENA region exists. Inclusion criteria Original studies will be included on interventions for all types of cancer which are available to support forcibly displaced populations in settings of humanitarian crisis in Djibouti, Egypt, Jordan, Lebanon, Mauritania, occupied Palestinian Territories, Somalia, Sudan, South Sudan, Syria, and Yemen. Methods A scoping review will be conducted in accordance with JBI methods and guidelines and PRISMA reporting guidelines (S3 Appendix). PubMed, Global Health, Embase, Scopus, The Lens, Global Index Medicus, and CINAHL Complete will be searched for peer-reviewed articles published from January to until present. IOM, ReliefWeb, OSCE, UNHCR, WHO, OCHA, and ACLED will be searched for grey literature. A dual review using three reviewers will independently identify all relevant articles and extract data from them. A narrative summary of findings will be reported, Discussion This scoping review will provide an overview of the available cancer interventions for forcibly displaced populations and describe the research done regarding these interventions. Potential gaps in the field will be identified, Systematic Review Registration Zenodo, https://doi.org/10.5281/zenodo.14633092